Proposals for Annual Plan 1966-67 Government of Andhra Pradesh - Planning Commission (Planning Commission, 1966)
The cost as per sanctioned Project estimates is Rs. 9112 lakhs. The cost of the Project as per the revised estimates sent to the Government of India in March 1962 is Rs. 13953 lakhs. The Project cost is likely to go up Rs. 14953 lakhs. The total requirements of foreign exchange for the Project have been brought down from Rs. 800 lakhs to Rs. 672 lakhs.
Planning Department, Government of Andhra Pradesh
Planning Department